Grain boundary interaction based on gradient crystal inelasticity and decohesion - Spannraft, Lucie; Ekh, Magnus; Larsson, Fredrik; Runesson, Kenneth; Steinmann, Paul (Computational Materials Science, 2020)
This paper presents a model for geometrically non-coherent grain boundary interaction premised on gradient-extended crystal inelasticity. The appropriate kinematics, the constitutive relations and the balance equations are established for a polycrystal including grain interaction. More specifically, this contribution proposes a coupling of the microtraction and grain boundary decoheion, which is represented as damage. As a consequence, decohesion exerts an impact on the standard tractions as well as on the microtractions along the grain boundaries. The appropriate modeling framework is assessed in terms of numerical results for a bicrystal that is subjected to simple shear. A comparison with the situation without such coupling effect shows that the microtractions along the grain boundary reduce for increasing damage and a microfree boundary is approached when the damage approaches unity.
CRIS-Team Scopus Importer:2020-03-17
Keywords: Boundary conditions; Decohesion; Gradient crystal plasticity; Grain boundary interaction